PROJECT-BASED LEARNING COLLABORATED WITH DIGITAL MEDIA FOR INDONESIAN EFL LEARNERS’ SELF-CONFIDENCE AND COMMUNICATION SKILL - Nazriani Lubis; Asnarni Lubis; Nurcantika Br Purba (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2020)
Indonesian EFL learners are still unconvinced to communicate by using English because being able to communicate requires the students to integrate self-confidence, and producing the meaningful idea at the same time. Fortunately, digital stuffs completely brings a new concept in ELT context since the use of digital in ELT clasroom can improve EFL learners’ communication skill. This research aims to reveal Indonesian EFL learners’ communication skill by integrating Project-based learning and digital media to siginificantly affect on students’ self-confidence on communication skill. To achieve the objective of the research, quantitative research method with factorial design 2X2 is applied. Then, the intruments used are interview with Likert scale and students’ communication achievement that have been distributed both normally and homogenously, thus, all the data are processed by using multivariate anova with sig 0,000 < 0,05. Based on the finding of the research, it is found that the using of Project-based Learning integrated with Telegram as media digital to share video absolutely affects on students’ communication skill because the students are able to think deeply in creating video project and feel comfortable to share with others on Telegram twice a week, it indicates that familiarity with their interlocutors and the community existed on Telegram group leads them to prefectly communicate with other in the real classroom context, and allows them to improve the ability to produce a meaningful idea to deliver.